Association of COL1A2 (PvuII) gene polymorphism with risk and severity of dental fluorosis - A case control study - C. Rahila; M.B. Aswath Narayanan; S.G. Ramesh Kumar; A. Leena Selvamary; A. Sujatha; J. John Kirubaharan (Elsevier, 2019)
Introduction: Dental fluorosis is a foremost public health problem in many countries, including India. Very few studies investigated gene polymorphism and risk of dental fluorosis. Genetic polymorphisms in Collagen Type I, alpha 2 (COL1A2) gene, found to be linked with bone pathogenesis, may affect the tooth formation resulting in the vulnerability to dental fluorosis. Aim: To assess the association between COL1A2 (PvuII) gene polymorphism and risk as well as severity of dental fluorosis. Methods: The present case control study was conducted among participants with (n = 60) and without (n = 60) dental fluorosis. Dental fluorosis was assessed using Modified Dean's fluorosis index (1942). The PvuII polymorphisms (in exon 25) inside the COL1A2 gene were genotyped by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) procedure. Statistical analysis were carried out with Chi-square test and Odds Ratio (OR) was determined with multivariate logistic regression analysis. Results: The genetic polymorphism in COL1A2 PvuII was found to be associated with the risk of dental fluorosis which was highly significant (p < 0.001). The odds ratio was 31.4 times [OR = 31.9, 95% CI: 3.9-48.7] higher for the homozygous PP genotype group and 4.0 times [OR = 4.0, 95% CI: 1.0-10.7] higher for the heterozygous Pp genotype. Conclusion: Genetic polymorphism of COL1A2 was found to be associated with dental fluorosis. The present study provides an insight for identification of the population who may subsist at risk of developing dental fluorosis in their later life. Keywords: COL1A2 gene, Dental fluorosis, Gene polymorphisms